Trust and Misinformation in Youth Digital Mental Health Information-Seeking in Kenya: Implications for Diagnosis Accuracy and Treatment-Seeking Behavior - Rosemary Odhiambo (International Journal of Psychological and Brain Sciences, 2026)
Digital platforms have become primary environments through which Kenyan youth seek mental health information, interpret psychological distress, and decide whether to pursue professional care. While digital mental health information-seeking can enhance awareness, reduce stigma, and provide immediate psychosocial support, the credibility of online content remains uneven, exposing youth to misinformation, unregulated pseudo-therapy, and algorithm-reinforced diagnostic narratives. This study examines how trust and misinformation shape youth digital mental health information-seeking in Kenya, with particular attention to implications for perceived diagnosis accuracy and treatment-seeking behaviour. A convergent mixed-methods design was employed, integrating quantitative survey data from 412 Kenyan youth aged 15–29 years, recruited through a combination of educational institutions, youth-focused organisations, and online platforms, 28 key informant interviews with mental health practitioners, educators, digital safeguarding actors, and youth programme implementers, and structured platform and document analysis across seven mainstream digital environments (Google Search, YouTube, TikTok, Instagram, WhatsApp, Facebook, and X/Twitter). Quantitative data were analysed descriptively to characterise prevalence patterns in digital help-seeking and self-diagnosis behaviours, while qualitative data were thematically analysed to contextualise trust formation, misinformation exposure, and governance gaps within everyday digital use. Results show that youth digital mental health engagement typically follows multi-platform pathways beginning with search-led self-triage and progressing into short-form social media spaces where identity-framed diagnostic content is highly prevalent. Over half of respondents reported adopting diagnostic labels following online exposure, based on self-perceived symptom alignment rather than clinical assessment, with identity-framing particularly pronounced in short-form feed environments. Trust was constructed primarily through relational and social heuristics—relatability (74%), confidentiality (69%), and peer endorsement (71%)—rather than professional verification cues (38%). Algorithmic amplification of symptom checklists and simplified diagnostic narratives increased diagnostic anchoring and self-label adoption, while simultaneously weakening transitions to formal mental health care. Ethical risks, including misinformation exposure (57%), privacy leakage (44%), unregulated counselling practices (39%), and weak crisis referral integration (61%), were widely reported across platforms. The findings highlight digital mental health information-seeking as both a protective and risky coping strategy for Kenyan youth. Strengthening perceived diagnostic understanding and appropriate treatment-seeking requires ecosystem-level interventions that embed credibility cues, algorithm-aware psychoeducation, safeguarding mechanisms, and referral pathways within everyday digital platforms. This study provides Kenya-specific evidence to inform youth-centred digital mental health governance and policy.